Kinerja Pemerintahan Nagari dalam Meningkatkan Pelayanan Masyarakat di Nagari Guguak Kecamatan Koto VII Kabupaten Sijunjung - Marlina, Nisa; Asril, Asril; Jamurin, Jamurin (Darul Yasin Al Sys, 2023)
This study aims to determine the performance of the nagari government in improving public services in Nagari Guguak, the efforts faced by the nagari government in improving community services in the Nagari Guguak and the obstacles faced by the nagari government in improving community services in Nagari Guguak, Koto VII District, Sijunjung Regency. The method used in this research is descriptive qualitative with the research location in the Guguak Wali Nagari Office, Koto VII District, Sijunjung Regency. The informants in this study were the Guguak Nagari Guardians, the Nagari Secretaries, the Nagari Officials, Community and Community Leaders. Data collection techniques are through observation, interviews and documentation. Data analysis techniques include data collection, data reduction, data presentation and drawing conclusions. The results of the study show that: The form of the performance of the nagari government in improving community services The nagari government should provide services to the community, namely it must prosper the community, but the following is contradictory because the nagari apparatus is slow in providing services to the community who takes care of their needs. the efforts faced by the nagari government in improving services to the community by making a suggestion box, because with this suggestion box the nagari apparatus can provide efforts to improve these services, the nagari apparatus provides a suggestion box and can also improve the quality of human resources (HR). the obstacles faced by the nagari government in improving community services are such as the low human resources (HR) of the nagari apparatus, the lack of public understanding of services that use the network and the internet causes problems with services. Based on the results of the research above, it can be concluded that the performance of the nagari government in improving services to the community is still not good. In an effort to improve these services, the nagari apparatus provides a suggestion box and can also improve the quality of human resources (HR). The constraints faced by the nagari government were constrained from carrying out service actions to the community. Due to the lack of good network and internet at the wali nagari office, the service is constrained which will make the community's NIB.